2016
DOI: 10.1371/journal.pone.0152538
|View full text |Cite
|
Sign up to set email alerts
|

DMSO Represses Inflammatory Cytokine Production from Human Blood Cells and Reduces Autoimmune Arthritis

Abstract: Dimethyl sulfoxide (DMSO) is currently used as an alternative treatment for various inflammatory conditions as well as for cancer. Despite its widespread use, there is a paucity of data regarding its safety and efficacy as well as its mechanism of action in human cells. Herein, we demonstrate that DMSO has ex-vivo anti-inflammatory activity using Escherichia coli- (E. coli) and herpes simplex virus-1 (HSV-1)-stimulated whole human blood. Specifically, we found that between 0.5%– 2%, DMSO significantly suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 47 publications
3
53
1
Order By: Relevance
“…DMSO solvent was used to dissolve the propofol powder, and then diluted to ensure that the concentration of DMSO would not damage the cells and affect our experimental results. It was reported that DMSO could alleviate the damage of ROS to cells [30]. However, DMSO, at the concentration needed to dissolve propofol as used in our experiment did not demonstrate the above mentioned beneficial effects, indicating that the beneficial effects observed are solely the effects of propofol.…”
Section: Discussioncontrasting
confidence: 60%
“…DMSO solvent was used to dissolve the propofol powder, and then diluted to ensure that the concentration of DMSO would not damage the cells and affect our experimental results. It was reported that DMSO could alleviate the damage of ROS to cells [30]. However, DMSO, at the concentration needed to dissolve propofol as used in our experiment did not demonstrate the above mentioned beneficial effects, indicating that the beneficial effects observed are solely the effects of propofol.…”
Section: Discussioncontrasting
confidence: 60%
“…Another study also reported the reduction of ERK phosphorylation, a kinase upstream of mTOR [31]. The effects observed here with 0.1% DMSO may indicate a proinflammatory response [101][102][103] with subsequent activation on mTOR [104,105].…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, oily formulations are not compatible with hydrophilic cell culture medium unless they are solubilized in organic solvents. The problem is that organic solvents can modify and alter the cellular response (Blachley et al, 1985;Luo et al, 1999;Elisia et al, 2016). In light of this, we developed a method that doesn't require any organic solvent.…”
Section: Discussionmentioning
confidence: 99%